SUPER- AND MACROSTRUCTURE OF POLISH, GREEK AND CYPRIOT NORMATIVE ACTS. A CONFRONTATIVE STUDY IN THE SCOPE OF TRANSLATION - GORTYCH-MICHALAK, Karolina (Comparative Legilinguistics, 2013)
Normative acts, together with the constitutions, are primary sources of law in the Polish and Greek legal systems. On the other hand, normative acts in the Cypriot legal system together with the Constitution of the Republic of Cyprus, the laws retained in force by virtue of Article 188 of the Constitution, the principles of Common Law and Equity, the laws enacted by the House of Representatives, are just some of the many sources of law in that state. Thus, in the three states mentioned above, the functions of the normative acts in question are different. With reference to this fact, the structures of normative acts are different too, although they are documents wherein rules regulating a certain domain of social life are drafted. The aim of this paper is to compare the structures of the normative acts analysed here in terms of Greek-Polish and Polish-Greek legal translation studies. The objective of comparing each structural element of the normative acts, and investigating their similarities and differences is to develop a model of applied contrastive analysis of legal texts for the purposes of legal translation studies. The application of this model of contrastive analysis provides concrete results in two fields of research: i) providing translation equivalents for legal terms connected with legal textology and ii) providing translation equivalents for the area of law to which the texts compared belong.